Original paperHydrocephalus induced via intraventricular kaolin injection in adult rats - Shaolin, Zhang; Zhanxiang, Wang; Hao, Xu; Feifei, Zhang; Caiquan, Huang; Donghan, Chen; Jianfeng, Bao; Feng, Liu; Shanghang, Shen (Folia Neuropathologica, 2015)
Hydrocephalus is a common neurological disease in humans, but a uniform and particularly effective hydrocephalic animal model amenable to proper appraisal and deep study has not yet been established. In this study, we attempted to construct a high-efficiency model of hydrocephalus via intraventricular kaolin injection. Adult male Sprague-Dawley rats were randomly divided into 2 groups: the control group (n = 15) and the experimental group (n = 30). Kaolin was injected into the lateral ventricle of experimental animals. Control rats underwent the same procedure but received sterile saline injection instead of kaolin. All animals with kaolin injection into the lateral ventricle developed hydrocephalus according to magnetic resonance imaging (MRI) results (success rate up to 100%). Also, the Morris water maze (MWM) test demonstrated disturbed spatial learning and memory. Furthermore, there were significant differences between groups with respect to the histological changes in the periventricular tissue. Our results indicate that experimental hydrocephalus induced by lateral ventricle injection of kaolin in adult rats is feasible and may be widely used.